KAWASAN WISATA OLAHRAGA ISLAM DI PEKANBARU DENGAN PENDEKATAN ARSITEKTUR BIOMIMETIK - Siti Aisyah; Wahyu Hidayat; Pedia Aldy (Jurnal Arsitektur ARCADE, 2020)
The Islamic Sports Tourism Area is quoted from a hadith which reads from Amir al-mu'minin, Umar Al-Faruq Ibn Al-Khattab, Rasulullah Shallallahu'alaihi Wasallam said: "Teach your children to ride, swim and archery". (HR. Shahih Bukhari / Muslim). From the hadith, 3 sports can be taken clearly from the Prophet Muhammad SAW, namely horse riding, swimming and archery. These three sports will be the main function in the Islamic sports tourism area. The design method used is a field survey and documentation as well as analyzing data. The results of the design take the formation of nature in general, namely leaves. The shape of nature is in line with the theme of this design, which is biomimetic architecture. In addition to the three main functions there are also supporting functions in the form of airsoft gun, all terrain vehicles, mosques, food courts, clinics, and retail. The Islamic sports tourism area aims to accommodate community activities and is the center of activities of Islamic Sports in Pekanbaru.).